Legal Istinbath Method of PERSIS in Modernism Spirit and Islamic Reformation - Asep Sopian (Karsa: Journal of Social and Islamic Culture, 2016)
This article proved that taking asbaab an nuzuul into consideration , and also paying attention to  the social , cultural, and historical background of the revelation, will lead to a more contextual intepretation of the quran. Meanwhile, the method of dragging out the law (istinbaath al hukm) are  successively through taking the  instruction of Quran, and then Hadist .  Personal opinion (ijtihad) is implemented when the law problem is not mentioned in the text (Quran or Hadist). The rise of different religious understanding between PERSIS and other Islamic religious organization was deeply influenced by the different methode of dragging law (istinbaath al hukm), the position of Nasakh-mansukh, the criteria of the Hadist validity, the position of hadist related to the fadlaail, position of asbaab an nuzuul and asbaa al wuruud,. Based on the findingand discussion of this methode of dragging law (istinbaath al jukm) and the Islamic legal decision (fatwa) of PERSIS, it.s proved that PERSIS is one of the Islamic reformation movement s which tends to understand religious text contextually.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i1.1002